2017
DOI: 10.1155/2017/8653286
|View full text |Cite
|
Sign up to set email alerts
|

RAPD Profiling, DNA Fragmentation, and Histomorphometric Examination in Brains of Wistar Rats Exposed to Indoor 2.5 Ghz Wi-Fi Devices Radiation

Abstract: The advent of Wi-Fi connected high technology devices in executing day-to-day activities is fast evolving especially in developing countries of the world and hence the need to assess its safety among others. The present study was conducted to investigate the injurious effect of radiofrequency emissions from installed Wi-Fi devices in brains of young male rats. Animals were divided into four equal groups; group 1 served as control while groups 2, 3, and 4 were exposed to 2.5 Ghz at intervals of 30, 45, and 60 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It is particularly known that long-term RF-EMF exposure can cause oxidative stress and also can alter some heat shock gene expressions in different types of cells. Ibitayo et al (2017) reported that weak fields can accelerate electron-sharing processes and consequently weaken H-bonding in cellular macromolecules [18]. This finding may explain the molecular and biochemical changes in the cells which are exposed to RF-EMF in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly known that long-term RF-EMF exposure can cause oxidative stress and also can alter some heat shock gene expressions in different types of cells. Ibitayo et al (2017) reported that weak fields can accelerate electron-sharing processes and consequently weaken H-bonding in cellular macromolecules [18]. This finding may explain the molecular and biochemical changes in the cells which are exposed to RF-EMF in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…The primers employed in this study have previously been used successfully in the assessment of variability in different species genotypes. OPT-06 and OPT-20 were used successfully in RAPD profiling and DNA fragmentation examination in brains of Wistar Rats (Ibitayo et al, 2017); genetic variability among Telfaira occidentalis, celosia argentea and Talinum triangulare (Bello et al, 2017). OPT-11 and OPT-20 were used in RAPD marker assessment of genetic diversity in citrullus colocynthis (L.) Schrad (Verma et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Today, children are among the frequent users of mobile devices such as smart phones and tablets. Mobile phones [ 1 - 4 ], mobile phone base stations [ 5 , 6 ], cordless phones [ 7 , 8 ], Wi-Fi connected devices [ 9 - 12 ], and power lines [ 13 ] are among the main sources of our daily exposures to electromagnetic fields. The rapid growth of wireless technology use has raised global public concerns especially for children [ 14 ].…”
Section: Introductionmentioning
confidence: 99%